2006
DOI: 10.5194/angeo-24-1375-2006
|View full text |Cite
|
Sign up to set email alerts
|

Imaging science at El Leoncito, Argentina

Abstract: Abstract. Thermospheric and mesospheric structures are studied using an all-sky imager located at El Leoncito, Argentina (31.8 • S, 69.3 • W, -18 • mag lat). This site has relatively high geographic latitude for a location under the crest of the equatorial ionization anomaly (EIA), and thus observations can be used to study the intrusion of several equatorial processes into the midlatitude domain. In addition, it has a conjugate point close to the field of view of our companion imager at Arecibo, PR, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 35 publications
6
52
0
Order By: Relevance
“…It should be noted that the Shiokawa et al (2003a) Another feature of our data is the relatively low occurrence rates recorded in Cerro Tololo, Chile, compared with the instrumentation in Hawaii. Low occurrence rates were also found by Martinis et al (2006) in El Leoncito, Argentina (−31.8 • N, 290.7 • E, dip = −31.5 • ), which is approximately 230 km southeast of Cerro Tololo. Analogous to CNFI and CASI located in Hawaii, the narrow field view of PICASSO observes lower geomagnetic latitudes compared to the allsky imager used in the Martinis et al (2006) study.…”
Section: Annmentioning
confidence: 97%
See 3 more Smart Citations
“…It should be noted that the Shiokawa et al (2003a) Another feature of our data is the relatively low occurrence rates recorded in Cerro Tololo, Chile, compared with the instrumentation in Hawaii. Low occurrence rates were also found by Martinis et al (2006) in El Leoncito, Argentina (−31.8 • N, 290.7 • E, dip = −31.5 • ), which is approximately 230 km southeast of Cerro Tololo. Analogous to CNFI and CASI located in Hawaii, the narrow field view of PICASSO observes lower geomagnetic latitudes compared to the allsky imager used in the Martinis et al (2006) study.…”
Section: Annmentioning
confidence: 97%
“…Low occurrence rates were also found by Martinis et al (2006) in El Leoncito, Argentina (−31.8 • N, 290.7 • E, dip = −31.5 • ), which is approximately 230 km southeast of Cerro Tololo. Analogous to CNFI and CASI located in Hawaii, the narrow field view of PICASSO observes lower geomagnetic latitudes compared to the allsky imager used in the Martinis et al (2006) study. In their study, Martinis et al (2006) observed MSTIDs in less than 5 % of the nights between 2000 and 2005.…”
Section: Annmentioning
confidence: 97%
See 2 more Smart Citations
“…Observations of electron density and minor constituent fluctuations may be detected by various instruments like incoherent scatter radar, ionosondes, all-sky airglow imagers, Global Positioning System (GPS) receivers, on site measurements, and satellite remote sensing [e.g., Nicolls et al, 2004;Brunini et al, 2004;Miró Amarante et al, 2004;Martinis et al, 2006;Earle et al, 2008;Wickert et al, 2009;Scheer and Reisin, 2010]. Near the Andes, at the El Leoncito Observatory (Argentina) (31.8°S, 69.3°W) where the main sources of GWs in the lower and middle atmosphere are found [Fritts and Alexander, 2003], Smith et al [2009] reported for the first time imaging observations of stationary mesospheric gravity waves in the nightglow emissions of OH, from all-sky images.…”
Section: Introductionmentioning
confidence: 99%